Quality of Life in Urban Neighborhoods in Jeddah, Saudi Arabia - Majrashi Abdulaziz, Abdurahman (La Tadeo Dearte, 2023)
Quality of life has become an increasingly important concept in recent times. Lately, the notion has received tremendous attention from governments, organizations, and decision-makers across the globe. The Kingdom of Saudi Arabia is one of the countries that have in recent years focused on improving the quality of life of its citizens and visitors through the Vision 2030 framework, under the Quality of Life Program. This study aims to assess the current situation in the Al-Aziziyah neighborhood in the city of Jeddah. An exploratory approach was employed to conduct the research. Sets of indicators were used to assess housing and circulation in the study area. The findings of the study revealed that quality of life has improved with the provision of quality housing, healthcare facilities, green/open spaces, and other related urban facilities/services. The findings are also in-line with the requirements of the Sustainable Development Goal (SDG) 11 for sustainable human settlements/cities. The study further recommends comparative studies between cities of the Kingdom and cities of nations with the best quality of life.